PEMOTONGAN DENGAN MENGGUNAKAN ABRASIVE WATERJET - Brodjonegoro, Satryo Soemantri; Nugroho, Yudhi P; Sutrimono, Sutrimono (Mesin, 1996)
Non-conventional cutting is required for quality production which is usually difficult to be achieved by conventional cutting. Besides non-conventional cutting provides advantages in simpliï¬ed cutting process and its ï¬exibility. This paper describes the theory of non-conventional cutting process using abrasive water-jet, the design and manufacturing of the cutter and also the performance testing.